The politics and economics of the transition period - Bukharin, Nikolai (Routledge library editions. Economics., 2003)
For many years a neglected figure, Nikolai Bukharin has recently been the subject of renewed interest in the West. Now regarded as a leading Marxist theorist, Bukharin's work has wide appeal to those interested in Soviet history and Marxist economics as well as to those concerned with theories of development and socialist economies.